2019
DOI: 10.1128/aac.00915-19
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of Cross-Resistance to Bedaquiline and Clofazimine following Treatment for Tuberculosis in Pakistan

Abstract: We report on the first six cases of acquired resistance to bedaquiline in Pakistan. Seventy sequential isolates from 30 drug-resistant-tuberculosis patients on bedaquiline-containing regimens were retrospectively tested for bedaquiline resistance by MIC testing and by the detection of mutations in relevant genes. We documented cases failing therapy that developed specific mutations in Rv0678 and had increased MICs associated with cross-resistance to clofazimine during treatment. This study underlines the relev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 12 publications
1
46
0
Order By: Relevance
“…Thus, the role of the Rv0678 and atpE in resistance is controversial, as mutations of these genes in susceptible and resistant strains have been reported. In other words, both susceptible and BDQ-resistant strains may carry mutations in these genes and the presence of mutations does not necessarily indicate resistance [32,63,64].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the role of the Rv0678 and atpE in resistance is controversial, as mutations of these genes in susceptible and resistant strains have been reported. In other words, both susceptible and BDQ-resistant strains may carry mutations in these genes and the presence of mutations does not necessarily indicate resistance [32,63,64].…”
Section: Discussionmentioning
confidence: 99%
“…The proposed combination may jeopardize treatment options for those patients, particularly if failure strains are resistant to both second-line core drugs: bedaquiline and FLQ [37]. Indeed, some small studies of bedaquiline-containing regimens show high rates of acquired drug resistance to bedaquiline: 24 out of 116 tests in Russia [38], and 6 out of 30 in Pakistan [39]. An alternative approach, applying the cascade of regimens concept, seems a better option: in TB treatment regimens, the core drug should be rifampicin when the strain is susceptible to rifampicin, a later generation FLQ in case of resistance to rifampicin, and bedaquiline if there is a resistance to FLQ [14].…”
Section: Discussionmentioning
confidence: 99%
“…However, our phenotypic and in silico results suggest that Leu117Arg affects the dimerization of Rv0678 causing a small increase but not high-level value of BDQ MIC. Other mutations in Rv0678 were described at the same codon position but with a different amino acid change ( 5, 8, 9, 11, 13 ). The Rv0678 mutations Val20Phe, Ala84Glu and Arg90Pro were observed to be linked to increase MICs for CLF and potentially associated to a BDQ-resistant phenotype, while Val20Gly was associated with both BDQ and CLF resistance ( 5, 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other mutations in Rv0678 were described at the same codon position but with a different amino acid change ( 5, 8, 9, 11, 13 ). The Rv0678 mutations Val20Phe, Ala84Glu and Arg90Pro were observed to be linked to increase MICs for CLF and potentially associated to a BDQ-resistant phenotype, while Val20Gly was associated with both BDQ and CLF resistance ( 5, 9 ). In this study, Rv0678 mutations Val20Ala and Ala84Val were found in BDQ-susceptible strains (MIC ≤ 0.008 µg/ml), while Arg90Cys was associated with a BDQ MIC value of 0.12 µg/ml.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation